2020
DOI: 10.1111/anae.14994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 6% hydroxyethyl starch 130/0.4 on kidney and haemostatic function in cardiac surgical patients: a randomised controlled trial

Abstract: Summary Whether third‐generation hydroxyethyl starch solutions provoke kidney injury or haemostatic abnormalities in patients having cardiac surgery remains unclear. We tested the hypotheses that intra‐operative administration of a third‐generation starch does not worsen postoperative kidney function or haemostasis in cardiac surgical patients compared with human albumin 5%. This triple‐blind, non‐inferiority, clinical trial randomly allocated patients aged 40–85 who underwent elective aortic valve replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
2
25
0
1
Order By: Relevance
“…Besides the theoretical framework, our favourable results are also supported by a previously reported retrospective exploratory analysis and a prospective randomised controlled trial [44,45]. In this study, the administration of HES was non-inferior to fluid resuscitation with albumin with regard to adverse kidney outcomes determined by biomarkers (urinary neutrophil gelatinaseassociated lipocalin and interleukin-18) as well as the 'Risk Injury Failure Loss End stage renal disease' (RIFLE) criteria [45]. Moreover, an earlier major prospective study concerning fluid management in intensive care even reported a lower mortality rate in patients when fluid resuscitation was achieved by the use of colloids (including HES) [13].…”
Section: Longitudinal Egfr Trajectories After Hes Administrationsupporting
confidence: 81%
See 2 more Smart Citations
“…Besides the theoretical framework, our favourable results are also supported by a previously reported retrospective exploratory analysis and a prospective randomised controlled trial [44,45]. In this study, the administration of HES was non-inferior to fluid resuscitation with albumin with regard to adverse kidney outcomes determined by biomarkers (urinary neutrophil gelatinaseassociated lipocalin and interleukin-18) as well as the 'Risk Injury Failure Loss End stage renal disease' (RIFLE) criteria [45]. Moreover, an earlier major prospective study concerning fluid management in intensive care even reported a lower mortality rate in patients when fluid resuscitation was achieved by the use of colloids (including HES) [13].…”
Section: Longitudinal Egfr Trajectories After Hes Administrationsupporting
confidence: 81%
“…a long intravascular half-life), HES appears to be another treatment option to achieve fast volume resuscitation with a low risk of fluid overload [15,17,42,43]. Besides the theoretical framework, our favourable results are also supported by a previously reported retrospective exploratory analysis and a prospective randomised controlled trial [44,45]. In this study, the administration of HES was non-inferior to fluid resuscitation with albumin with regard to adverse kidney outcomes determined by biomarkers (urinary neutrophil gelatinaseassociated lipocalin and interleukin-18) as well as the 'Risk Injury Failure Loss End stage renal disease' (RIFLE) criteria [45].…”
Section: Longitudinal Egfr Trajectories After Hes Administrationsupporting
confidence: 71%
See 1 more Smart Citation
“…Diese gründen aber z. T. auf älteren Daten, die nur bedingt auf die heutige Zeit übertragen werden können [55]. Verschiedene aktuelle, aber kleine klinische Studien zeigen keine klaren Vorteile einer Therapie mit Albumin 5 % hinsichtlich allgemeiner Morbidität und Organfunktion im Vergleich mit HES bei großen abdominalchirurgischen [56], urologischen [57] oder herzchirurgischen [58] Eingriffen. Im Gegensatz fand sich in einer großen, retrospektiven Kohortenstudie eine signifikant reduzierte Krankenhaussterblichkeit, aber kein Einfluss auf die Inzidenz von Nierenfunktionsstörungen bei mittels Albumin 5 % behandelten herzchirurgischen Patienten [59].…”
Section: Humanalbumin Perioperativunclassified
“…However, in spite of a lively scientific debate over the last two decades, the perioperative use of synthetic colloids remains a controversial issue [3][4][5][6][7]. Following two studies published in 2012 [8,9], the European Medicine Agency (EMA) and the US Food and Drug Administration (FDA) issued warnings that hydroxyethyl starch (HES) should no longer be used in critically ill patients due to a possible rise in kidney injury and mortality associated with the administration of HES [10,11].…”
Section: Introductionmentioning
confidence: 99%